EFFECT OF BENIGN PROSTATIC HYPERPLASIA ON MORPHOLOGICAL CHANGES IN THE WALL OF THE BLADDER - O.V. Shmulichenko (Bogomolets National Medical University, 2017)
Benign prostatic hyperplasia (BPH) is the most common cause of infravesical obstruction in men, but not the only one. The number of patients with prostatic hyperplasia in the world and in Ukraine is constantly increasing [2]. According to the Institute of Urology of the Academy of Medical Sciences of Ukraine, the prevalence of PH in Ukraine in 2013 was 1132.9 per 100 thousand of the adult male population. [9]. The hyperplastic prostate creates an obstacle to the flow of urine from the bladder. It includes not only a mechanical factor - compression, deformation, erroneous elongation of the proximal urethra and a change in the urethrovesic angle, but also a violation of the circulation.